After Socrates. Leo Strauss and the Esoteric Irony - Basili, Cristina (Anales del Seminario de Historia de la Filosofía, 2020)
Throughout the philosophical tradition that stems from Plato, Socratic irony has represented an enigma that all interpreters of the Platonic dialogues have had to face from different points of view. In this article I aim to present the peculiar Straussian reading of Socratic irony. According to Leo Strauss, Socratic irony is a key element of Plato’s political philosophy, linked to the «logographic necessity» that rules his texts. I will therefore examine the genesis and the main features of Straussian hermeneutics. I will end the article by highlighting the relevance of the esoteric interpretation of Platonic thought as a conceptual tool that responds to the crisis of modern political philosophy.